(untitled) (Innovative professional education, 2025)
The article deals with the actual issues of using innovative technologies in the educational process of students in artistic implementing professional pre-higher education institutions. The main tasks of a competitive specialist in the labor market are defined, meeting the needs of the globalized modern environment while taking into account the possession of reguired skills, including social competencies